Association of Neighborhood-Level Material Deprivation With Atrial Fibrillation Care in a Single-Payer Health Care System: A Population-Based Cohort Study. Issue 3 (9th June 2022) - Abdel-Qadir, Husam; Akioyamen, Leo E.; Fang, Jiming; Pang, Andrea; Ha, Andrew C.T.; Jackevicius, Cynthia A.; Alter, David A.; Austin, Peter C.; Atzema, Clare L.; Bhatia, R. Sacha; Booth, Gillian L.; Johnston, Sharon; et al.
Abstract : Background: There are limited data on the association of material deprivation with clinical care and outcomes after atrial fibrillation (AF) diagnosis in jurisdictions with universal health care. Methods: This was a population-based cohort study of individuals ≥66 years of age with first diagnosis of AF between April 1, 2007, and March 31, 2019, in the Canadian province of Ontario, which provides public funding and prohibits private payment for medically necessary physician and hospital services. Prescription medications are subsidized for residents >65 years of age. The primary exposure was neighborhood material deprivation, a metric derived from Canadian census data to estimate inability to attain basic material needs. Neighborhoods were categorized by quintile from Q1 (least deprived) to Q5 (most deprived). Cause-specific hazards regression was used to study the association of material deprivation quintile with time to AF-related adverse events (death or hospitalization for stroke, heart failure, or bleeding), clinical services (physician visits, cardiac diagnostics), and interventions (anticoagulation, cardioversion, ablation) while adjusting for individual characteristics and regional cardiologist supply. Results: Among 347 632 individuals with AF (median age 79 years, 48.9% female), individuals in the most deprived neighborhoods (Q5) had higher prevalence of cardiovascular disease, risk factors, and noncardiovascular comorbidity relative to residents of the least deprived neighborhoods (Q1). After adjustment, Q5 residents had higher hazards of death (hazard ratio [HR], 1.16 [95% CI, 1.13–1.20]) and hospitalization for stroke (HR, 1.16 [95% CI, 1.07–1.27]), heart failure (HR, 1.14 [95% CI, 1.11–1.18]), or bleeding (HR, 1.16 [95% CI, 1.07–1.25]) relative to Q1. There were small differences across quintiles in primary care physician visits (HR, Q5 versus Q1, 0.91 [95% CI, 0.89–0.92]), echocardiography (HR, Q5 versus Q1, 0.97 [95% CI, 0.96–0.99]), and dispensation of anticoagulation (HR, Q5 versus Q1, 0.97 [95% CI, 0.95–0.98]). There were more prominent disparities for Q5 versus Q1 in cardiologist visits (HR, 0.84 [95% CI, 0.82–0.86]), cardioversion (HR, 0.80 [95% CI, 0.76–0.84]), and ablation (HR, 0.45 [95% CI, 0.30–0.67]). Conclusions: Despite universal health care and prescription medication coverage, residents of more deprived neighborhoods were less likely to visit cardiologists or receive rhythm control interventions after AF diagnosis, even though they exhibited higher cardiovascular disease burden and higher risk of adverse outcomes.